Cognitive Levels in TOEFL iBT Reading: A Bloom’s Revised Taxonomy Approach - Romadhon, Romadhon (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2024)
This study aims to analyze the cognitive demands of the TOEFL iBT reading section utilizing the application of Bloom’s Revised Taxonomy. 80 reading comprehension questions from four practice tests were categorized into cognitive levels, ranging from lower-order thinking skills (LOTS) to higher-order thinking skills (HOTS). The findings reveal a predominant focus on LOTS, with Understanding and Remembering constituting 53.75% and 16.25% of the questions, respectively. In contrast, HOTS, such as Analyzing and Evaluating, account for only 30% of the total questions, while the Creating level is absent. The absence of Creating in the reading section reflects the test’s design, which prioritizes objective and time-efficient assessment methods, such as multiple-choice questions. Tasks that require creative responses are more time-consuming and subject to subjective evaluation, making them less feasible in standardized testing environments. The study concludes that while the TOEFL iBT reading section effectively measures foundational reading skills, it may not fully capture the higher-order cognitive processes essential for academic success. Expanding the assessment to include more HOTS and exploring methods to incorporate Creating tasks could provide a more comprehensive evaluation of students' academic readiness.